2005
DOI: 10.1097/01.gme.0000172265.40196.86
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring reproductive aging in a 5-year prospective study: aggregate and individual changes in steroid hormones and menstrual cycle lengths with age

Abstract: Aggregate-level analyses show general changes in steroid hormones and cycle length but cannot show variation within and across women. Individuals' cycle lengths were too variable to predict hormone levels. Clinicians should obtain more data on individual women's hormonal patterns when determining fertility or menopause treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 42 publications
3
68
1
Order By: Relevance
“…Participant and nonparticipant data were presented previously. 32 For this analysis, 67 women were postmenopausal for the entirety of their participation in the BIMORA project, and 89 women had at least one menstrual bleed during the project.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participant and nonparticipant data were presented previously. 32 For this analysis, 67 women were postmenopausal for the entirety of their participation in the BIMORA project, and 89 women had at least one menstrual bleed during the project.…”
Section: Resultsmentioning
confidence: 99%
“…Specimens were self-collected and shipped to the laboratory for analysis. 32 Urinary levels of the ALH and AFSH subunits were assayed in duplicate using sandwich immunoenzymometric assays (IEMA) 34 ; they were highly correlated with serum LH and FSH (intact) results. 34 The urinary LH IEMA measured total free ALH; all urine specimens were heated for 2 minutes before assay to dissociate intact LH into its free A and > subunits.…”
Section: Data Collection and Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…At longer time scales, interindividual variation in age-dependent changes in hormone levels is also evident, e.g. in human females, Ferell et al (2005) showed that population-level analyses of steroid hormone and menstrual cycle changes do not accurately predict relationships within and among individual women. Thus, the principles of homeostasis notwithstanding, large (5-to 10-fold) inter-individual variation is the norm for hormone titres and some endocrine-mediated traits at all temporal scales.…”
Section: How Large Is Inter-individual Variation In Endocrine Traits?mentioning
confidence: 99%